(untitled) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: Global tectonics, which has been formed by rotational processes, is determined by a stable regmatic network (tectonic frame) and structures of the central type (ring and vortex). Lithospheric plates are global vortex systems caused by the tectonic mass flow. Vortex structures are tectonic complexes that capture the results of a combination of vertical and horizontal tectonic movements and which can be recorded by direct geological observations. Methodology: The purpose of the research is to obtain a general understanding of global geodynamics using lineament analysis, fundamental research data, and original developments of the authors. Results and discussion: Vortex structures is the main type of tectonic elements of the Earth, they offer a key to understanding its geological evolution. They started to form during the nuclear stage of the planet’s development. Displacement of the upper shells of the Earth relative to each other always leave “impressions” of previously existing deep structures (ring, vortex, fault structures). Ring and vortex structures are characterised by high permeability and are often magma-controlling and ore-bearing. There is a paragenetic relationship between vortex and ring structures. The depression of the Pacific Ocean is a vortex megastructure. Ring structures may represent the final stage of the development of the tectonic vortex when its branches (“arms”) had joined the core. Examples of lithospheric vortices are marginal seas in the West Pacific, which were formed as a result of the tectonic interaction of the Eurasian and Pacific lithospheric plates due to a velocity shear. Conclusion: The described ideas provide a new understanding of the tectonic evolution of the West Pacific “continent-ocean” transition zone as a lithospheric vortex megastructure.